2017
DOI: 10.1007/s10877-017-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Four-wavelength near-infrared peripheral oximetry in cardiac surgery patients: a comparison between EQUANOX and O3

Abstract: Near-infrared spectroscopy (NIRS) is a continuous and noninvasive technology that measures regional tissue oxygen saturation (rSO). A new 4-wavelength generation of NIRS monitors is now available. We aimed to compare peripheral somatic rSO values given by the 4-wavelength EQUANOX™ 7600 device (Nonin Medical Inc., Plymouth, Mn) and O3™ device (Masimo Corporation, Irvine, CA). Twenty adult patients scheduled for conventional elective cardiac surgery with cardiopulmonary bypass over a 4-month period were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…baseline StO 2 , before initiation a VOT), all observed dynamic characteristics (both the down- and upslope part of the VOT) turned out to be different. Similarly, the study of Ferraris et al [4] discussed above found significant differences from individual baseline StO 2 values during a VOT between the two devices studied (Masimo O3 and Nonin EQUANOX, respectively). These clear observations indicate that differences in NIRS techniques itself (e.g.…”
Section: Near Infrared Spectroscopysupporting
confidence: 51%
See 1 more Smart Citation
“…baseline StO 2 , before initiation a VOT), all observed dynamic characteristics (both the down- and upslope part of the VOT) turned out to be different. Similarly, the study of Ferraris et al [4] discussed above found significant differences from individual baseline StO 2 values during a VOT between the two devices studied (Masimo O3 and Nonin EQUANOX, respectively). These clear observations indicate that differences in NIRS techniques itself (e.g.…”
Section: Near Infrared Spectroscopysupporting
confidence: 51%
“…Another method comparison study on NIRS devices was published by Ferraris et al [4] in the same issue. Although such devices are primarily developed for cerebral oximetry, the authors compared peripheral (somatic) StO 2 values obtained on the forearm with two different last generation four-wavelength NIRS devices in 20 adult patients undergoing elective cardiac surgery at several predefined time points.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Theoretically, NIRS devices that use more wavelengths would be more accurate and have enhanced tissue recognition [21]. However, no published studies have examined the superiority of 4-wavelength NIRS systems over others, DOI: 10.1159/000510072 and since no reference value exists for measuring peripheral tissue oxygen saturation, it is difficult to say whether 1 NIRS device is more accurate than another [16]. Second, despite the technological similarities, the optical technology and computational algorithms that are used to derive actual oxygen saturation values may differ between devices, and these values are derived from various assumptions that may not be error free [21].…”
Section: Discussionmentioning
confidence: 99%
“…INVOS ® (Somanetics Corp., Troy, MI, USA) was developed for measuring regional brain oxygen saturation through the use of 2 light-emitting diodes [13], and IN-VOS ® has also been widely used to obtain tissue oxygen saturation in areas other than the brain and peripheral microcircular reactivity measurements using VOT [1,2,14]. O3 TM (Massimo Corp., Irvine, CA, USA) is a recently developed NIRS method that uses 4 wavelengths, and only a few studies have used this device to measure cerebral oxygen saturation [15] or StO 2 [16]. For NIRS devices, oximetry values are calculated using an assumed cerebral or tissue arterial:venous ratio (A/V ratio).…”
Section: Introductionmentioning
confidence: 99%
“…However, measurement of the orthostatic blood volume accumulation in the small vessels is more challenging. To track intravascular orthostatic volume changes within the small blood vessels of the lower leg, a new four-wavelength generation NIRS monitor has been used (Ferraris et al 2018). NIRS tissue oxygen saturation measurement is made on a mixture of both venous and arterial blood with a mean ratio of this mixture estimated to be 70% venous–30% arterial (Benni et al 2018).…”
Section: Discussionmentioning
confidence: 99%